2023
DOI: 10.1038/s41418-023-01226-w
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SMURF2 expression enhances RACK1 stability and promotes ovarian cancer progression

Yanan Pi,
Qiushi Feng,
Fusheng Sun
et al.

Abstract: Receptor for activated C kinase 1 (RACK1) has been confirmed to take part in multiple biological events and the mechanism supporting abnormal RACK1 expression in ovarian cancer (OC) remains to be characterized. Here, we identified Smad ubiquitin regulatory factor 2 (SMURF2) as a bona fide E3 ligase of RACK1 in OC. SMURF2 effectively added the K6, K33 and K48 ubiquitin chains to the RACK1, resulting in polyubiquitination and instability of RACK1. PCAF promoted acetylation of RACK1 at K130, leading to SMURF2-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The results presented in this study underscore the effectiveness of SBSGL in suppressing the malignant characteristics of HB cells. Specifically, SBSGL impedes HB tumour growth by inhibiting the O‐GlcNAcylation of RACK1, which is involved in multiple signalling pathways, affecting processes such as cell growth and migration and is aberrantly expressed in a wide range of malignant tumours 36 . Notably, O‐GlcNAcylation is also closely associated with the malignant phenotype of tumours, with a recent study highlighting the critical role of O‐GlcNAcylation in influencing tumour cell proliferation, metastasis, and angiogenesis 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented in this study underscore the effectiveness of SBSGL in suppressing the malignant characteristics of HB cells. Specifically, SBSGL impedes HB tumour growth by inhibiting the O‐GlcNAcylation of RACK1, which is involved in multiple signalling pathways, affecting processes such as cell growth and migration and is aberrantly expressed in a wide range of malignant tumours 36 . Notably, O‐GlcNAcylation is also closely associated with the malignant phenotype of tumours, with a recent study highlighting the critical role of O‐GlcNAcylation in influencing tumour cell proliferation, metastasis, and angiogenesis 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, SBSGL impedes HB tumour growth by inhibiting the O‐GlcNAcylation of RACK1, which is involved in multiple signalling pathways, affecting processes such as cell growth and migration and is aberrantly expressed in a wide range of malignant tumours. 36 Notably, O‐GlcNAcylation is also closely associated with the malignant phenotype of tumours, with a recent study highlighting the critical role of O‐GlcNAcylation in influencing tumour cell proliferation, metastasis, and angiogenesis. 37 Furthermore, elevated O‐GlcNAcylation levels have been observed in breast cancer tissues, impacting intercellular adhesion and promoting migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting ubiquitination may lead to stabilization of RACK1 at protein level and increased expression. Another research indicated that in ovarian cancer (OC), Smad ubiquitin regulatory factor 2 (SMURF2) was abnormal low expression, resulting in decreased ubiquitination of RACK1 and increased stability [ 33 ]. The development of cholangiocarcinoma is coordinated by complex interactions of extracellular ligands (such as pro-inflammatory cytokines, growth factors, bile acids, among others) present in the tumor microenvironment, increased expression and/or abnormal activation of cell surface receptors and disturbances of intracellular signaling pathways, ultimately leading to cell proliferation, survival, and genetic and/or epigenetic changes [ 1 ]; So we could think that a single gene RACK1 need to produce the cancer-promoting mechanism under certain auxiliary conditions.…”
Section: Discussionmentioning
confidence: 99%
“…RACK1 could enhance the ability of self-renewal and chemoresistance of cancer stem cells in human hepatocellular carcinoma [19] and was reported to facilitate the development and lymph node metastasis of cervical cancer [21]. Besides, RACK1 may promote the ability of proliferation and the tendency of invasion and metastasis of breast cancer [22], and the decrease of ubiquitin degradation of RACK1 in ovarian cancer leads to the enhancement of the proliferation, migration, and invasion of ovarian cancer cells [23]. In the central nervous system, some studies have shown that RACK1 promotes the proliferation and invasion of glioma cells and may also affect the differentiation and apoptosis of glioma cells [24,25], but so far there are no studies on RACK1 in meningiomas.…”
Section: Introductionmentioning
confidence: 99%
“…CSNK2B is a regulatory subunit of casein kinase 2, which regulates the catalytic activity of this kinase [26,27]. Some studies have shown that CSNK2B can activate the NF-κB pathway [28], which in turn promotes the expression of cell cycle-related proteins and facilitates the transformation of the cell cycle [23]. This process is thought to drive the proliferation of tumor cells and contribute to their malignant progression.…”
Section: Introductionmentioning
confidence: 99%